The challenges of recovering from individual and cultural trauma in Toni Morrison’s "Home" - Ibarrola, Aitor (International Journal of English Studies, 2014)
The journey back home to Lotus, Georgia, that the protagonist of Morrison’s latest novel, Frank Money, undertakes is planted with too many obstacles to turn it into the kind of “reconnecting experience” that would help him to recover from the traumas he suffers from. Frank’s sense of alienation is exacerbated by some hateful childhood memories, his participation in the Korean War and his painful losses there, the failure to support the woman he loves, and the racism that he still experiences in the U.S. of the 1950s. Home (2012) offers amplegrounds to discuss topics such as acts of remembrance, memory traces, the politics of mourning, and direct (and indirect) representations of trauma and sorrow. Yet, the main question the novel poses is to what extent Frank’s journey to rescue his younger sister, Cee, helps him to achieve some kind of redemption and whether that redemption is fully materialized at the end of the novel. doi: http://dx.doi.org/10.6018/ijes/14/1/179921